2008
DOI: 10.1111/j.1600-0714.2008.00646.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral manifestations in patients with gastro‐oesophageal reflux disease: a single‐center case–control study

Abstract: This study failed to find any significant association between GERD and dental erosions, whereas some symptoms and other objective oral mucosal changes were found to be significantly associated with GERD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
2
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 62 publications
1
80
2
6
Order By: Relevance
“…this erythema and mucosal atrophy may be present as a result of chronic exposure of tissues to acid (5). Oral complaints GERD patients often mention other oral complaints such as sensitation of burning or heat in the mouth, halitosis, xerostomia, dysgeusia -foul taste, and dental sensitivity related to hot or cold drinks or foods due to the erosions (5,9,18,20).…”
Section: Oral Mucosa Lesionsmentioning
confidence: 99%
“…this erythema and mucosal atrophy may be present as a result of chronic exposure of tissues to acid (5). Oral complaints GERD patients often mention other oral complaints such as sensitation of burning or heat in the mouth, halitosis, xerostomia, dysgeusia -foul taste, and dental sensitivity related to hot or cold drinks or foods due to the erosions (5,9,18,20).…”
Section: Oral Mucosa Lesionsmentioning
confidence: 99%
“…5,14 However, other studies have proposed a significant relationship between halitosis and GERD (Table 4). [16][17][18][19]29 16,29 In these studies, the erosive reflux disease group had higher VSC values than the NERD group. However, these studies lacked a true control group, such as healthy subjects.…”
Section: Discussionmentioning
confidence: 72%
“…5 Recently, gastroesophageal reflux disease (GERD) has been reported to be one of the causes of halitosis. [15][16][17][18][19] Moreover a study has reported that GERD-related symptoms were associated with halitosis, regardless of the oral conditions. 17 In contrast, some studies have reported that halitosis is not associated with erosive GERD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 This condition may worsen if bad oral hygiene is associated. 5,6 The detection of these oral lesions in GERD patients is a top priority; considering the link between lesion severity and acid reflux disease, an effective management of oral pH is needed.…”
Section: Discussionmentioning
confidence: 99%